Abnormal pulmonary function tests are associated with prolonged ventilation and risk of complications following elective cardiac surgery. Issue 6 (November 2019) - Reddi, Benjamin AJ; Johnston, Sonya D; Bart, Stanley; Chan, Justin CY; Finnis, Mark
Elective cardiac surgery accounts for a significant proportion of perioperative resource allocation in Australasia. Preoperative pulmonary function testing (PFT) is routinely undertaken in some centres to identify patients who may require prolonged ventilation and intensive care unit (ICU) stay, although there are currently no data supporting this practice. Routine PFT places a burden on respiratory diagnostic laboratories, is inconvenient to patients and may delay surgery. We aimed to identify whether PFT parameters identify patients requiring prolonged mechanical ventilation after elective cardiac surgery. Adult patients admitted to the Royal Adelaide Hospital ICU following elective cardiac surgery between July 2013 and December 2017 were identified retrospectively from the local ICU database. Preoperative PFT and operative and postoperative outcome data were retrieved from local databases, and multivariable logistic regression was undertaken to identify which PFT variables were associated with prolonged mechanical ventilation. PFT data were available for 835/1139 (73%) elective cardiac surgical cases. The best independent predictors of prolonged mechanical ventilation were post-bronchodilator forced vital capacity (FVC) and single-breath diffusing capacity for carbon monoxide (DL CO). Patients with FVC <80% predicted and DL CO <60% predicted had an odds ratio for prolonged postoperative ventilation of 7.5 (95% confidence intervals 3.6–15.6; P  < 0.001). The area under the receiver operating characteristic curve derived from this model was 0.68. Abnormal PFT results were associated with prolonged postoperative mechanical ventilation. A PFT-based prediction tool does not accurately predict individual patient outcome but identifies a cohort of patients at higher risk of requiring prolonged ventilation, potentially informing ICU resource allocation and surgical planning.